Mrs. Morris and the pot of gold - Wilton, Traci (Wilton, Traci. Salem B&B Mystery, 2022)
"Salem, Massachusetts, B&B owner Charlene Morris will need the luck of the Irish--and the help of a ghost--to unveil a hooded killer . . . Charlene has hired a van to ferry her B&B guests to an all-you-can-eat corned beef and cabbage dinner hosted by Salem's Irish community at the Ancient Order of Hibernians club--but she should have booked a hearse. It's never a good sign when the family black sheep drunkenly crashes a party by punching the guy dressed as a leprechaun. But things go from troublesome to fatal when Charlene stumbles upon a second brawl in an upper room--and this fight Connor Gallagher loses, his anonymous assailant rushing past Charlene, hidden by a hoodie. Now Detective Sam Holden has another homicide on his hands, with Charlene as the only eyewitness. Even if she can't give the police sketch artist much to go on, Charlene is determined to ID the murderer, with the help of Dr. Jack Strathmore, the charming ghost who haunts her B&B. The answer lies in the motive, and to uncover that sleuth and spook will need to shine a light on Connor's shady past--before the killer pulls another Irish goodbye . . ."--